Leading change : a guide to whole systems working - Attwood, Margaret (Policy Press, 2003)
Many policy makers have become reliant on mechanistic top-down audit and inspection regimes as the means of implementing public service reforms. This innovative book sets out to redress the balance. I It outlines the theory behind whole systems development and gives good practice guidance on how to effectively develop 'systems' to improve joined-up working.